Unraveling Subcellular and Ultrastructural Changes During Vitrification of Human Spermatozoa: Effect of a Mitochondria-Targeted Antioxidant and a Permeable Cryoprotectant - Kumar, Pradeep; Wang, Mengying; Isachenko, Evgenia; Rahimi, Gohar; Mallmann, Peter; Wang, Wanxue; Brandenstein, Melanie von; Isachenko, Vladimir (Frontiers in Cell and Developmental Biology, 2021)
Mitochondria-targeted antioxidants have great potential to counterbalance the generated reactive oxygen species (ROS) because they cross the inner membrane of mitochondria. Still, their use was not reported in vitrified human spermatozoa. Our laboratory has successfully vitrified spermatozoa without the use of permeable cryoprotectants, but subcellular level evidence was missing. Therefore, this study aimed to improve spermatozoa vitrification using mitochondria-targeted antioxidants (Mito Q) and reveal ultrastructural changes in spermatozoa due to the use of permeable cryoprotectants and report alteration of functional proteins during the spermatozoa vitrification process. For this, each of 20 swim-up-prepared ejaculates was divided into seven aliquots and diluted with vitrification medium supplemented with varying concentrations of Mito Q (0.02 and 0.2 µM), glycerol (1, 4, and 6%), and a combination of Mito Q and glycerol. All aliquots were vitrified by the aseptic capillary method developed in our laboratory. The spermatozoa function assays revealed that the addition of either Mito Q (0.02 µM), glycerol (1%), or a combination of Mito Q (0.02 µM) and glycerol (1%) in vitrification medium results in better or equivalent spermatozoa quality relative to the control. Transmission electron microscopy revealed that Mito Q protects spermatozoa from undergoing ultrastructural alteration, but glycerol induced ultrastructural alteration during the vitrification process. Next, we performed label-free quantitative proteomics and identified 1759 proteins, of which 69, 60, 90, and 81 proteins were altered in the basal medium, 0.02 µM Mito Q, 1% glycerol, and Mito-Glycerol groups, respectively. Actin, tubulins, and outer dense fiber proteins were not affected during the vitrification process. Some of the identified ubiquitinating enzymes were affected during spermatozoa vitrification. Only a few proteins responsible for phosphorylation were altered during vitrification. Similarly, several proteins involved in spermatozoa-egg fusion and fertilization (IZUMO1, Tektin) were not affected during the vitrification process. In conclusion, Mito Q attenuates vitrification-induced ultrastructural changes and alteration in key proteins involved in spermatozoa functions and fertilization.